Comparison of Serum Visfatin Levels in Post-Menopausal Pakistani Women with and Without Breast Carcinoma - Gohar, Lubna; Ahmed, Umbreen; Zafar, Nadeem; Wahid, Mansoor; Shoaib bin Aleem; Junaid, Shazia (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare serum Visfatin levels in Pakistani post-menopausal women having breast carcinoma with healthy women.Study Design: Comparative cross-sectional study.Place and Duration of Study: Physiology Department, Army Medical College, in collaboration with Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from Dec 2019 to Dec 2020.Methodology: Eighty post-menopausal Pakistani women were included, out of which forty women were post-menopausal newly diagnosed and histologically confirmed cases of breast carcinoma awaiting their treatment. Menopause was confirmed through interviews and relevant history. Serum Visfatin levels were determined using an enzyme-linked immunosorbent assay (ELISA).Result: Mean serum Visfatin levels were significantly higher in the Breast Carcinoma-Group (28.14±8.17 ng/ml) compared to the Healthy Control-Group (13.64±1.07 ng/ml). Moreover, serum Visfatin levels correlated positively with weight (r=0.735), body mass index (r=0.678), waist circumference(r=0.295) and waist-to-hip ratio (r=0.220).Conclusion: Serum Visfatin levels were markedly elevated in post-menopausal women with breast carcinoma as compared toHealthy Controls. Higher serum Visfatin may be regarded as a potential risk factor in the development of breast carcinoma.